ANTENATAL THALASSAEMIA SCREENING – DETERMINING THE APPROPRIATE MEAN CORPUSCULAR VOLUME (MCV) CUT-OFF FOR EXCLUDING ALPHA THALASSAEMIA. (February 2015) - Lee, Koon; Cheung, Carol
Abstract : Background and aim: Thalassaemia trait cannot be unequivocally excluded based on MCV > 80fL alone, and screening laboratories may issue comments such as 'alpha thalassaemia trait/normal A2 beta thal trait cannot be excluded'. This causes downstream logistic issues particularly in the management of antenatal patients. We undertook a pilot study to assess if liberally investigating those patients and their partners with MCV between 80-86fL would capture any additional at-risk pregnancies. Method: A 1 year retrospective analysis of antenatal thalassaemia screening requests is performed. When stated, partners are included for analysis. Genetic testing results are reviewed for couples electing to proceed with genetic testing. Results and discussion: In total, 634 females were screened; 45% of whom had MCV values between 80–86 fL. Partners of this cohort were invited for screening, with 47% ( n  = 137) screened. Genetic testing proceeded in only 3 couples – two where the male partners had heterozygous HbE with low HbVar%. One couple gave the history of a previously affected child. None required prenatal diagnosis or other intervention. Conclusion: Permissive screening of antenatal women with MCV up to 86fL results in minimal impact in terms of genetic testing or clinical outcome. Routine screening of male partners is more effective for risk assessment.